Function of ORFC of the polyketide synthase gene cluster on fatty acid accumulation in Schizochytrium limacinum SR21 - Yanyan Shi; Zhen Chen; Yixin Li; Xingyu Cao; Lijie Yang; Yiyuan Xu; Zhipeng Li; Ning He (Biotechnology for Biofuels, 2021)
Abstract Background As a potential source of polyunsaturated fatty acids (PUFA), Schizochytrium sp. has been widely used in industry for PUFA production. Polyketide synthase (PKS) cluster is supposed to be the primary way of PUFA synthesis in Schizochytrium sp. As one of three open reading frames (ORF) in the PKS cluster, ORFC plays an essential role in fatty acid biosynthesis. However, the function of domains in ORFC in the fatty acid synthesis of Schizochytrium sp. remained unclear. Results In this study, heterologous expression and overexpression were carried out to study the role of ORFC and its domains in fatty acid accumulation. Firstly, ORFC was heterologously expressed in yeast which increased the PUFA content significantly. Then, the dehydratase (DH) and enoyl reductase (ER) domains located on ORFC were overexpressed in Schizochytrium limacinum SR21, respectively. Fatty acids profile analysis showed that the contents of PUFA and saturated fatty acid were increased in the DH and ER overexpression strains, respectively. This indicated that the DH and ER domains played distinct roles in lipid accumulation. Metabolic and transcriptomic analysis revealed that the pentose phosphate pathway and triacylglycerol biosynthesis were enhanced, while the tricarboxylic acid cycle and fatty acids oxidation were weakened in DH-overexpression strain. However, the opposite effect was found in the ER-overexpression strain. Conclusion Therefore, ORFC was required for the biosynthesis of fatty acid. The DH domain played a crucial role in PUFA synthesis, whereas the ER domain might be related to saturated fatty acids (SFA) synthesis in Schizochytrium limacinum SR21. This research explored the role of ORFC in the PKS gene cluster in Schizochytrium limacinum and provided potential genetic modification strategies for improving lipid production and regulating PUFA and SFA content.